The impact of an unexpected wage cut on corruption: Evidence from a "Xeroxed" exam - Oana Borcan; Mikael Lindahl; Andreea Mitrut (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper aims to understand how corruption responds to an income loss. We exploit an unexpected 25% wage cut incurred in 2010 by all Romanian public sector employees, including the public education staff. We investigate a corruptible high-stake exam taking place shortly after the wage announcement. To measure corruption we compare changes in exam outcomes from 2009 to 2010 between public and private schools, as the latter were not affected by the policy. We find that the wage loss induced better exam outcomes in public than in private schools and we attribute this difference to increased corruption by public educators.
Keywords: I20; H70; J30; 330; public educators; bribes; high-stakes exam; Korruption; Lehrkräfte; Besoldung; Bildungsniveau; Vergleich; Privatschule; Schätzung; Rumänien